Effects of increasing doses of activated recombinant factor VII on haemostatic parameters in swine - Pusateri, Anthony E.; Ryan, Kathy L.; Delgado, Angel V.; Martinez, Raul S.; Uscilowicz, John M.; Cortez, Douglas S.; Martinowitz, Uri (Thrombosis and Haemostasis, 2005)
This study examined dose-response relationships between activated recombinant factorVII (rFVIIa) and (1) in vivo haemostasis and (2) in vitro measures of coagulation and platelet function. Anesthetized swine were used. Ear bleeding time (BT) was measured and blood was sampled following increasing doses of rFVIIa (0, 90, 180, 360 and 720 μg/kg; n = 6) or saline (n = 6). BT was not altered by rFVIIa. Prothrombin time (PT) using standard or pig-specific methods was decreased by rFVIIa. Activated clotting time (ACT) was decreased by rFVIIa. Thromboelastography using collagen (COLL) or pig thromboplastin (p-ThP) as agonist demonstrated shorter reaction times, shortened time to reach maximum velocity of clot formation, and increased α -angle in the presence of rFVIIa. rFVIIa dosing increased maximum velocity of clot formation when p-ThP was used to initiate the reaction but not when COLL was used. rFVIIa at the highest concentration increased maximum amplitude when COLL was used to initiate the reaction. Platelet aggregation was not altered by rFVIIa. Following completion of the dose escalation phase, a severe liver injury was produced. rFVIIa altered neither blood loss nor survival time following injury but improved mean arterial pressure. A small increase in systemic thrombin-antithrombin III complex occurred after administration of rFVIIa at doses of 180 μg/kg and above. However, there was no histological evidence of intravascular coagulation after rFVIIa administration. In summary, rFVIIa activity was detectable in vitro but did not change haemostasis in normal swine.
Keywords: Pharmacological haemostasis; liver injury; trauma; thromboelastography